The Surety of God's Promises: A Theological Interpretation of Genesis 22. (August 2019) - Campbell, Stephen D.
The account in Genesis 22 of Abraham's binding and near sacrifice of his son Isaac is one of the best known passages in all of the Old Testament and presents the reader with a perfect example of the difficulty of achieving the "correct" interpretation of a given text. This essay attempts to offer a fresh interpretation of Genesis 22 that closely attends to the text, moves beyond purely descriptive objectives, wrestles with the questions that the text itself raises, and is motivated by theological concerns. This process begins by placing this text within the Abrahamic narrative of Genesis. In the final assessment, it is argued that when theological concerns are given a voice, this text depicts at least three theological realities. First, this text shows that Yhwh is a God who allows his servants to experience trials. Second, it demonstrates the nature of true faith through the example of Abraham. The faith that Abraham demonstrated is exemplary precisely because of the challenges that he faced. And third, it displays—perhaps surprisingly to the modern reader—the faithfulness of God, for this episode shows that God's choice of Abraham is not arbitrary. Moreover, Genesis 22 demonstrates that when God makes promises, he must be faithful to keep those promises.